2021
DOI: 10.2174/1871527319666200905122222
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Heart Rate Variability and Parkinson’s Disease: A Meta-analysis

Abstract: Aim: A systematic review which aims to assess the evidence regarding the function of the autonomic heart rate regulation system among Parkinson‟s disease (PD) patients. The main objective of the study is to compare heart rate variability (HRV) between those with and without PD from published studies. The subgroup analyses aimed to investigate the impact of treatment and disease duration on heart rate variability (HRV), assessed by measuring sympathetic and parasympathetic activity via low-frequency (LF) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…However, it remains unclear why heart rate did not signi cantly increase during FOG for the mDT condition. We speculate that saturation effects might have played a role: autonomic cardiovascular dysfunction is prevalent in Parkinson's disease, resulting in lower heart rate variability, thereby preventing a further increase of the already high baseline levels (40). Because the cDT included an episodic type of DT, namely starting or stopping based on episodic auditory stimuli, this condition had lower heart rate baseline levels and therefore a signi cant heart rate increase during FOG.…”
Section: Heart Ratementioning
confidence: 98%
See 1 more Smart Citation
“…However, it remains unclear why heart rate did not signi cantly increase during FOG for the mDT condition. We speculate that saturation effects might have played a role: autonomic cardiovascular dysfunction is prevalent in Parkinson's disease, resulting in lower heart rate variability, thereby preventing a further increase of the already high baseline levels (40). Because the cDT included an episodic type of DT, namely starting or stopping based on episodic auditory stimuli, this condition had lower heart rate baseline levels and therefore a signi cant heart rate increase during FOG.…”
Section: Heart Ratementioning
confidence: 98%
“…The difference in heart rate change between FOG and stopping counted only 1.78 bpm on average, so devices should be able to detect differences of approximately 1-2 bpm. Secondly, autonomic dysfunction is prevalent in PD and some patients might take beta-adrenergic blocking agents for tremor reduction, thereby blunting possible cardiovascular responses (40). As a consequence, variances in heart rate might become so small that even very precise monitors are not able to detect relevant changes.…”
Section: Recommendationsmentioning
confidence: 99%
“…Heart rate variability (HRV) derived estimates of cardiac parasympathetic activity have been observed to be reduced in patients with PD (Kallio et al, 2000;Buob et al, 2010;Sabino-Carvalho et al, 2018;Li et al, 2020) independent of the measurement duration/experimental circumstance. However, this finding is not unanimous (Oka et al, 2011;Kiyono et al, 2012;Vianna et al, 2016).…”
Section: Parasympathetic Dysfunction In Pdmentioning
confidence: 99%
“…Despite the fact that most indices derived from HRV primarily reflect vagal function, the joint analysis of the low frequency (LF) component, expressed in normalized units, and the LF/HF ratio, has been suggested to be an acceptable marker of sympathetic modulation (Malliani et al, 1994) although this has been challenged (Parati et al, 2006). In this regard, a decreased LF (Li et al, 2020), LF/HF ratio at rest (Oka et al, 2011;) and a blunted increase in LF/HF ratio during tilt-table testing (Friedrich et al, 2010), has been identified in patients with PD compared to controls. However, this result is not unanimous, and other studies have not observed LF/HF ratio to be decreased at rest in PD (Bouhaddi et al, 2004;Friedrich et al, 2008;Vianna et al, 2016;Sabino-Carvalho et al, 2018).…”
Section: Sympathetic Dysfunction In Pdmentioning
confidence: 99%
“…Heart rate variability in PD is vastly investigated with traditional linear parameters, which indicate diminished sympathetic and parasympathetic autonomic activity (Jain, 2011;Jain and Goldstein, 2012;Soares et al, 2013;Maetzler et al, 2015;Gibbons et al, 2017;Palma and Kaufmann, 2018;Akbilgic et al, 2020;Li et al, 2020). Only a few studies on non-linear parameters of heart rate variability (HRV) in PD are available in pre-existing literature (Kallio et al, 2002;Pursiainen et al, 2002;Palma and Kaufmann, 2018), though non-linear parameters of HRV are widely used to study other kinds of pathologies (Voss et al, 2009;Shaffer and Ginsberg, 2017).…”
Section: Introductionmentioning
confidence: 99%